Ruptured Rudimentary Horn Pregnancy at 25 Weeks with Previous Vaginal Delivery: A Case Report - Deepa V. Kanagal; Lokeshchandra C. Hanumanalu (Case Reports in Obstetrics and Gynecology)
Unicornuate uterus with rudimentary horn occurs due to failure of complete development of one of the Mullerian ducts and incomplete fusion with the contralateral side. Pregnancy in a noncommunicating rudimentary horn is extremely rare and usually terminates in rupture during first or second trimester of pregnancy. Diagnosis of rudimentary horn pregnancy and its rupture in a woman with prior vaginal delivery is difficult. It can be missed in routine ultrasound scan and in majority of cases it is detected after rupture. It requires a high index of suspicion. We report a case of G2PlL1 with rupture rudimentary horn pregnancy at 25 weeks of gestation which was misdiagnosed as intrauterine pregnancy with fetal demise by ultrasound, and termination was attempted and the case was later referred to our hospital after the patient developed hemoperitoneum and shock with a diagnosis of rupture uterus. Laparotomy revealed rupture of right rudimentary horn pregnancy with massive hemoperitoneum. Timely laparotomy, excision of the horn, and blood transfusion saved the patient.